Deep‐Ultraviolet LEDs Incorporated with SiO2‐Based Microcavities Toward High‐Speed Ultraviolet Light Communication. Issue 23 (16th September 2022) - Yu, Huabin; Memon, Muhammad Hunain; Jia, Hongfeng; Ding, Yifan; Xiao, Shudan; Liu, Xin; Kang, Yang; Wang, Danhao; Zhang, Haochen; Fang, Shi; Gong, Chen; Xu, Zhengyuan; et al.
Abstract: Optical wireless communication (OWC) in the deep‐ultraviolet (DUV) band requires an efficient DUV light source with large bandwidth characteristics. In this work, a feasible approach is reported to enlarge the light output power as well as the bandwidth of a DUV light‐emitting diode (LED) by embedding a SiO2 ‐based microcavity on which an aluminum (Al) reflector is simultaneously deposited. Consequently, on the one hand, the microcavity with the Al‐reflector can facilitate photon escape from the LED to increase the light extraction efficiency, thus enhancing the light output power of the devices. On the other hand, the LED incorporated with a microcavity structure exhibits a reduced resistance–capacitance time constant, leading to an increase in the modulation bandwidth of the LED. Strikingly, the DUV LED incorporated with microcavities represents a significant enhancement of light output power by nearly 30% at 80 mA while exhibiting a higher modulation bandwidth of 12% in comparison to the conventional LED without microcavities. Thus, the implementation of the microcavity and Al reflector on top of a classic LED can enlarge the light output power and modulation bandwidth, eventually facilitating to establish viable high‐speed OWC systems. Abstract : SiO2 ‐based microcavities are fabricated into deep ultraviolet light‐emitting diodes (DUV LEDs) while depositing aluminum reflectors on top of devices. The microcavity with the Al‐reflector can increase the light extraction efficiency, thus enhancing the light output power of the devices. Simultaneously, the LED incorporated with microcavities exhibits a higher modulation bandwidth due to the reduced resistance–capacitance time constant.